The exorcist. Believer [videorecording (DVD)] - Abbasi, Amman; Wingo, David (Universal, 2023)
Since the death of his pregnant wife in a Haitian earthquake 12 years ago, Victor Fielding has raised their daughter, Angela on his own. But when Angela and her friend Katherine, disappear in the woods, only to return three days later with no memory of what happened to them, it unleashes a chain of events that will force Victor to confront the nadir of evil and, in his terror and desperation, seek out the only person alive who has witnessed anything like it before: Chris MacNeil.